2004
DOI: 10.1111/j.1600-051x.2004.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma TGF‐β1 as a risk factor for gingival overgrowth

Abstract: Furthermore, concomitant treatment with calcium channel blockers did not influence the levels of plasma TGF-beta1 in the patients group. The relationship between gingival overgrowth, independent periodontal variables and TGF-beta1 plasma concentrations was examined using univariate and multivariate regression analyses; low TGF-beta1 plasma concentrations were found to be a risk factor for gingival overgrowth in immunosuppressed patients concomitantly receiving a calcium channel blocker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…Ellis et al (2004) reported a lower plasma TGF‐ β 1 concentration in patients with GO. They found a significantly inverse correlation between plasma levels of TGF‐ β 1 and GO, suggesting that patients are at a greater risk of more severe overgrowth with a lower, rather than a higher, TGF‐ β 1 concentration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ellis et al (2004) reported a lower plasma TGF‐ β 1 concentration in patients with GO. They found a significantly inverse correlation between plasma levels of TGF‐ β 1 and GO, suggesting that patients are at a greater risk of more severe overgrowth with a lower, rather than a higher, TGF‐ β 1 concentration.…”
Section: Discussionmentioning
confidence: 96%
“…However, the latter type of overgrowth is not predominantly fibrotic and the pathology can result from deficiency of this cytokine. In the latest investigation, in which the influence of periodontal status and TGF‐ β 1 plasma concentration on GO was analysed, the low plasma level of this cytokine was found to be a risk factor of GO in patients receiving CsA and concomitantly calcium channel blockers (Ellis et al 2004).…”
mentioning
confidence: 99%
“…Although studies 17‐19 on matrix metalloproteinase (MMP)‐1, interleukin (IL)‐6, and the drug transporter MDR1 gene failed to identify any association with gingival overgrowth, other studies 20‐22 identified clear associations between polymorphisms in α2 integrin, transforming growth factor (TGF)‐β1, and IL‐1 and gingival overgrowth. In the case of TGF‐β1, serum levels were a significant indicator of the risk for developing gingival overgrowth 23 …”
Section: Discussionmentioning
confidence: 99%
“…TGF-1 pro-fibrotic role could be explained also by the stimulation of collagen synthesis in lamina propria. There are considerable data supporting the fact that under pathological conditions, TGF-1 orchestrates a cross talk between parenchymal, inflammatory and collagen expressing cells and have a key role in control inflammation and fibrosis (Buduneli et al, 2001b;Ellis et al, 2004;Wright et al, 2001). The role of TGF-1 in gingival overgrowth must be considered in line with natural development of the periodontal lesion, as inflammation preceedes fibrosis, and with its stadial activity.…”
Section: B) Transforming Growth Factor-β (Tgf-β)mentioning
confidence: 99%